Increased serum prolactin in borderline personality disorder - Atmaca, Murad; Korkmaz, Sevda; Ustundag, Bilal; Ozkan, Yusuf (Sage Publications Inc, 2015)
Although there is an important interaction between serotonergic system, prolactin and suicidal behavior, and impulsivity, no investigation examined the prolactin values in borderline personality disorder in which suicidal behavior and impulsivity are core symptom dimensions. In this context, in the present investigation, we planned to measure serum prolactin levels in the patients with borderline personality disorder. The study comprised 15 patients with borderline personality disorder and 15 healthy controls. Prolactin values were measured in both patients and control subjects. The patients had abnormally higher mean value of prolactin compared to those of healthy controls (48.66 +/- 36.48mg/dl for patients vs. 15.20 +/- 7.81mg/dl for healthy controls). There was no correlation between prolactin values and any demographic variables for both the patients and control subjects. In conclusion, our present results suggest that prolactin values increased in the patients with borderline personality disorder and are required to be replicated by more comprehensive and detailed further studies to decipher the exact roles of prolactin increase.
Keywords: Prolactin; borderline personality disorder; serotonin